The Rate and Risk Factors of Acute Kidney Injury among Cancer Patients’ Admissions in Palestine: A Single-Center Study - Zaher Nazzal; Fatima Abdeljaleel; Aseel Ashayer; Husam Salameh; Zakaria Hamdan (International Journal of Nephrology)
Introduction. Acute kidney injury (AKI) remains a critical issue for cancer patients despite recent treatment improvements. This study aimed to assess the incidence of AKI in cancer patients and its related risk factors. Methods. A Retrospective cohort study was conducted at tertiary hospitals in the period 2016–2018. A data abstraction sheet was used to collect related variables from patients’ records. During admission, the incidence of AKI was assessed using creatinine measurements. RIFLE criteria were used to classify it into five categories of severity: risk, injury, failure, loss, and end-stage renal disease. Results. Using RIFLE (Risk, Injury, Failure, Loss, and End-stage renal disease) criteria, 6.9% of admissions were complicated with AKI. The severity of these fell into the categories of risk, injury, and failure, 3.3%, 1.7%, and 1.9%, respectively. In the multivariate model, the odds for developing AKI was significantly higher for patients with congestive heart failure (AOR = 17.1, 95% CI 1.7–80.1), chronic kidney disease (adjusted OR = 6.8, 95% CI 1.4–32.2 (P value 0.017)), sepsis (AOR = 4.4, 95% CI 1.9–10.1), hypercalcemia (AOR = 8.4, 95% CI 1.3–46.1), and admission to the ICU (AOR = 5.8, 95% CI 2.1–16.2). In addition, the mortality rate was nearly seven times higher for patients complicated by AKI (relative risk = 7.6, 95% CI 3.2–18.2). Conclusion. AKI was significantly associated with congestive heart failure, chronic kidney disease, sepsis, ICU admission, and hypercalcemia in cancer patients, resulting in poorer outcomes and higher mortality rates. AKI assessment for hospitalized cancer patients should be performed regularly, especially for patients at increased risk.